Informal Networks and Start-Up Entrepreneurs in Spain: Networking Other Entrepreneurs and Angel Investors - Aliaga-Isla, Rocío (2014)
This paper contributes by containing an examination of the impact of informal networks, such as personally knowing other entrepreneurs and having access to business angel investors, have upon start-up entrepreneurs in Spain. In addition, a pseudo-panel approach is used with micro data from the Spanish Global Entrepreneurship Monitor (GEM) adult population survey over the period 2006-2009. This technique overcomes limitations found when using cross-sectional data. Moreover, this includes a short review of literature using cross-sectional data in order to identify how researchers used these data. Results show that informal networks are important for start-up entrepreneurs. Knowing other entrepreneurs personally and having access to angel investors have a positive relationship with start-up entrepreneurs. Also, the findings indicate that startup entrepreneurs in cohorts aged 49-58 and 59-64 do better than younger ones. Furthermore, this article highlights some implications.